Study on Indonesian plastic marine debris based on river survey. Issue 1 (April 2021) - Abidin, A Z; Steven, S
Abstract: In response to Jambeck's claim on Indonesian plastic marine debris, some academicians, scientists, as well as associations such as The Indonesian Olefin and Plastic Industry Association (INAPLAS), Indonesian Plastic Recycle Association (ADUPI), and Indonesian Plastic Recycle Industry Association (APDUPI) conducted a deeper plastic balance examination to clarify and enlight the Indonesian plastic marine debris amount. This study continued the previous work, which employed the river survey method to conduct a more accurate calculation in the actual condition. From the river survey results, Indonesian plastic marine debris amount is about 0.038 MT/y and it will reduce to 0.004 MT/y if the trash trap is strictly-applied. This result is not much different compare to the seashore approach but again also clarifies that Indonesia is not the second-largest contributor country for plastic marine debris. Moreover, asides from conserving the marine and river environments, installing a trash trap on the river could increase local people's income at once.